Metafora Al-Qur’an: Majaz Mursal dalam Surat Asy-Syu’ara’ - Lu'lu Abdullah Afifi; Edi Komarudin (UIN Sunan Gunung Djati Bandung, 2021)
Metaphor in the Qur'an is a form of beauty in the language of the holy book which is one part of literary construction. In addition, it also influences the interpretation. In parrot science it is called majaz. The style of language that puts the meaning of the branch on the original meaning, such as the majaz mursal in the letter Asy-Syu'ara which is meticulously written. The reason for the author to research and study it is, first, the style of majaz influences, expands the meaning of the wording in the Qur'an and understands the meaning desired by Allah Swt. Second, it has implications for translation and interpretation. Third, in the Surah Ash-Syu'ara, Allah Swt uses majaz in the verse of the doom of the previous prophets. Fourth, the verses are interesting both in sentence composition and rhetorically (balāghiyyah). This study uses a descriptive-analytical method of majaz mursal in surah Asy-Syu'ara, using a linguistic approach, especially balagah, by analyzing the verses in the letter, detailing the types of majaz mursal and its 'alāqah, explaining the interpretation and message. From this research, it can be seen, first, in the letter Asy-Syu'ara, there are two majaz mursal in two verses, namely in QS. Ash-Syu'ara: 105 with 'alāqah kulliyah and in QS. Ash-Syu'ara: 208 with 'alāqah mahalliyyah. Second, the two verses depart with different contexts, as well as different themes. In verse 105, regarding Noah's people who denied Noah and the teachings of monotheism. Meanwhile, verse 208 deals with polytheists who reject the Qur'an and ask Allah SWT to hasten the punishment. In addition, the language of majaz is also used in conveying stories as ibrah or lessons. For example in the story of Noah.